IC 9467 - Analyses Of Mobile Equipment Fires For All U. S. Surface And Underground Coal And Metal/Nonmetal Mining Categories, 1990-1999 - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
This report analyzes mobile equipment fires for all U.S. surface and underground coal and metal/nonmetal mining categories by state and 2 year time periods during 1990-1999. Risk rate values are derived, and ignition source, methods of fire detection and suppression, and other variables are examined. The data were derived from MSHA mine fire accident publications and verbal communications with mine personnel. The analyses will provide the National Institute for Occupational Safety and Health (NIOSH), the Mine Safety and Health Administration (MSHA), and the mining industry with a better understanding of the hazards associated with mobile equipment fires and will create a basis for future fire research programs.